Evaluation of Plant-Based Acaricides for Tick Control in Cattle: A Sustainable Alternative - Sadhu, Dashrath B; Patel, Om S; Sadariya, Kamlesh A.; Rao, Neha M; Raval, Sunant K. (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Tick infestations pose a major challenge, reducing animal health, productivity, and profitability while also transmitting haemoprotozoan and rickettsial diseases. Excessive reliance on chemical acaricides has led to environmental concerns, harm to non-target species, and the emergence of acaricide-resistant ticks, necessitating sustainable alternatives. This study evaluated the acaricidal efficacy of deltamethrin as standard treatment, polyherbal readymade spray, aqueous extracts from Annona squamosa (sugar apple), and Polyalthia longifolia (Ashoka) as eco-friendly tick control measures. A total of 71 cattle was selected and assessed for tick counts, haematological parameters, and cortisol levels. The study revealed the highest tick reduction with polyherbal readymade spray, followed by the combined and individual plant extracts with significant improvement in haematological parameters in treated groups by Day 28, while untreated cattle showed reverse trend. Similarly, cortisol level, elevated due to infestation, normalized in treated groups but worsened in controls, indicating persistent stress. These findings highlight the potential of plant-based acaricides as effective and sustainable alternatives for tick management in cattle.